EFL Teachers’ Interpretation and Practices under Indonesia’s K-13 Curriculum: A Qualitative Case Study in an Elementary School - Nurlaily Nurlaily; Maya Marsevani; Leil Badrah Zaki (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2025)
The implementation of English language instruction in elementary schools under the K-13 curriculum has become widespread, yet there is limited understanding of how teachers interpret and apply the curriculum in their classrooms. This study aims to explore elementary school English teachers' interpretations of the K-13 curriculum and their pedagogical strategies. Adopting a qualitative descriptive approach, data were collected through classroom observations and structured interviews with three English teachers at the elementary level. The data were analyzed thematically, revealing key patterns in teaching strategies and challenges. Teachers reported using interactive methods, such as group discussions, student-centered activities, and technology integration, to engage students effectively. However, they faced significant challenges, including inadequate teaching resources, large class sizes, and limited time, all of which hindered the full implementation of the curriculum. These findings underscore the need for targeted professional development programs and improved resource allocation to address these challenges. The study provides actionable insights for policymakers and educators aiming to optimize English language teaching within the K-13 framework, emphasizing the importance of supporting teachers in overcoming obstacles to effective curriculum delivery.